Developing Experimental of Dimple Effect Applied on Flat Plate against Fluid Flow - Irfan Syarif Arief; Rachmadi Wahyu Adjie (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2019)
Dimple is a concave commonly seen on a golf ball. These concaves turn out to have an effect on the movement of the golf ball so as to help the golf ball fly further. From the advantages of golf balls, whether the cavity can help to reduce the friction of the hull with the water surface. This study aims to determine the effect of dimple on flat plate with different types of flow (laminar, transition, and turbulent) and how it affects the coefficient of friction (Cf). In addition, with the difference in the ratio of the concavity (Rc) how it affects the coefficient of friction (Cf). From these influences later we can know how the optimal dimple design on the hull of the ship. The simulation method will be done with Numeca Fine Open. This software can simulate the complicated shape dimple well than any other software. The result of the analysis will be known to decrease the coefficient of friction (Cf) during laminar flow, transition, and turbulent. With a growing influence when turbulent flow. In addition, the greater the ratio of the concentration will decrease the coefficient of friction greater than the small-scale ratio.